Arabic Language Learning Management in Improving The Language Proficiency of STEI Permata Bojonegoro Students - Muflihatin, Siti Imaniatul; Nadhif, Moh. (Global Education Journal, 2025)
This study aims to examine the implementation of Arabic language learning management in order to enhance the language skills of MTs students at STEI Permata. Data were collected through interviews and documentation. The findings indicate that the four core management functions—planning, organizing, implementing, and evaluating—have been effectively carried out. The planning function includes coordination, time allocation, development of annual and semester programs, as well as syllabus and lesson plan formulation. The organizing function involves placement tests, scheduling for both regular and special classes, and the assignment of teachers based on their competencies. The implementation is conducted by adapting teaching techniques to students’ language proficiency levels. The evaluation function is carried out by assessing both the process and outcomes of each language skill (maharah). Supporting internal factors include the active participation of special class students in completing assignments, while external factors consist of student placement based on academic ability and teachers’ readiness to adjust learning strategies during the pandemic.